Generating Unit Tests for Floating Point Embedded Software using Compositional Dynamic Symbolic Execution - Prelgauskas, J.; Bareisa, E. (Elektronika ir Elektrotechnika, 2012)
We present a method that would integrate both: compositional dynamic symbolic execution and search-based test data generation methods to achieve better code coverage for software that largely depends on floating point computations. We have implemented our method as an extension of a well-know symbolic execution engine – PEX. Our extension implements search-based testing as an optimization technique using AVM method. We present coverage comparison for several benchmark functions. Ill. 1, bibl. 17, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1814